Development of a training package on clinical teaching for consultants of an integrated pediatric residency training program - Concepcion, Blesilda E.
The training of residents is vital to ensure delivery of quality patient care. To achieve this aim, clinical teachers must possess the necessary competencies to enable them to fulfill a range of key roles in the training process. Hence, it is important that they be provided with the appropriate teacher training programs. This research and development study was conducted in the Department of Pediatrics of four tertiary medical centers in Metro Manila affiliated with First Integrated Residency Training Pediatric Program Inc. (F.I.R.S.T. Inc.). This is a consortium of four hospitals namely, Cardinal Santos Medical Center, The Medical City General Hospital, Our Lady of Lourdes Hospital and Victor R. Potenciano Medical Center whose goals are centered on collaborative training, research and service. The study primarily aimed to design a training package on clinical teaching for consultants of F.I.R.S.T. A needs assessment survey was initially done of active regular consultants of F.I.R.S.T. to determine their personal, academic and professional profile, the core topics to be incorporated in the training package and their preferred format and schedule of training sessions. Results showed that the consultants of FIRST Inc. considered the skills on planning the teaching process, knowing and using the different clinical teaching methods and assessing the residents as either important or very important and should be included in the training package. The following units of instruction were designed: The Residents as Learners, Planning the Teaching Process, Facilitating the Learning Process, Evaluating Resident's Learning and Utilizing Media Effectively. The instructional design for each unit was formulated. It is recommended that this training package on clinical teaching be implemented for consultants of FIRST as an integral part of its staff development program.